STRATEGI KOMUNIKASI DALAM MEPERTAHANKAN EKSISTENSI WAYANG KULIT PADA BERSIH DESA (STUDI PADA RITUAL BERSIH DESA DI DESA SIRAMAN KECAMATAN KESAMBEN KABUPATEN BLITAR) - Andiwi Meifilina (Program Studi Ilmu Komunikasi, 2021)
Bersih Desa is a hereditary tradition in Javanese culture. Bersih Desa is a form of the union of humans with nature and a form of gratitude to the Creator, namely God Almighty. Clean Village can be defined as a form of gratitude for both the harvest, health, and prosperity. So in the Bersih Desa event, a shadow puppet cultural art performance is always held. The existence of shadow puppets in Java until now shows that they are still popular in the midst of the audience. The ability of wayang kulit to survive from generation to generation is something that proves that wayang kulit is an art that not only contains Javanese cultural values ​​but is a personal need for wayang kulit fans because wayang kulit shows have messages and advice conveyed to the audience. The ability of wayang kulit that persists in the midst of modernization and globalization, socioculturally this wayang kulit adapts to developments in society. Psychologically, wayang kulit is still firmly attached to the minds of its fans. The shadow puppet show in Bersih Desa event must still exist in the community so it is very important to have a communication strategy in maintaining its existence, one of which is in Bersih Desa event to preserve the local cultural heritage of the ancestors. This study uses a descriptive qualitative method regarding communication strategies in maintaining the existence of wayang kulit at Bersih desa, with the support of literature studies and observations or observations of wayang kulit performances. Data was collected using interviews, literature and documentation. By using a descriptive method, the results of the communication strategy in maintaining the existence of wayang kulit at Bersih desa can be described in depth, detail and holistically. The communication strategy in maintaining the existence of wayang kulit at Bersih Desa is carried out by planning communication (communication planning) and communication management (communicatiom management) to achieve a goal. Communication strategy planning is carried out by covering: a.) Identify the target audience,b.) Build what you want to achieve c.) Think about what should be included in the message d.) How much commitment is required, smutual respect for intergenerational culture so as to create a good correlation. e.) Choose the right media channel, f.) Communication plan, to provide information to g.) Measure the success achieved, h.) The communication program that has been implemented needs to be evaluated to find out the extent of the success achieved, Communication management oncommunication strategy in maintaining the existence of wayang kulit at Bersih Desa carried out with activities including: implementation activities, organizing, directing, controlling, influencing the level of success, recipients, successful communication strategies or not, it is necessary to review the implementation of communication activities, effective & efficient on communication strategies, supporting factors for wayang kulit.